PERSONNEL PLANNING. A COMPARATIVE OUTLOOK - Catalin Constantin SAMOILA (Journal of Defense Resources Management, 2015)
From a very wide perspective, planning has raised lots of issues over time. Management and business theory struggle to teach what planning is, and why it is so dramatically important, in a manner which seemingly quotes Antoine de Saint-Exupery -“A goal without a plan is just a wish”, or sets up awareness through Benjamin Franklin’s famous words -“By failing to prepare, you are preparing to fail” [1]. However, some voices are circumspect or balance between the usefulness of plans and planning: “… plans are useless, but planning is indispensable” [2], while others, sporadically but decisively, criticize the entire organizational planning process, presenting it as a total failure [3]. Sometimes the ‘cons’ are right, meaning that real life might bring more surprise than ever expected. Even so, organizations benefit from planning by trying at least to ‘see’ one step forward, and to avoid total uncertainty or critical situations, if not to improve. The military ones are not exempt. Military planning has become the organic environment for such organizations since Napoleonic wars, or even longer ago. This present attempt does not intend to deeply analyze the antagonist advocacies over planning, but to bring under comparison, in a brief manner, the business-shaped theoretical approach of planning, against the real concerns of the Romanian military system in terms of manpower planning.